In Vitro Analyses of Spinach-Derived Opioid Peptides, Rubiscolins: Receptor Selectivity and Intracellular Activities through G Protein- and β-Arrestin-Mediated Pathways - Yusuke Karasawa; Kanako Miyano; Hideaki Fujii; Takaaki Mizuguchi; Yui Kuroda; Miki Nonaka; Akane Komatsu; Kaori Ohshima; Masahiro Yamaguchi; Keisuke Yamaguchi; Masako Iseki; Yasuhito Uezono; et al. (Molecules, 2021)
Activated opioid receptors transmit internal signals through two major pathways: the G-protein-mediated pathway, which exerts analgesia, and the β-arrestin-mediated pathway, which leads to unfavorable side effects. Hence, G-protein-biased opioid agonists are preferable as opioid analgesics. Rubiscolins, the spinach-derived naturally occurring opioid peptides, are selective δ opioid receptor agonists, and their p.o. administration exhibits antinociceptive effects. Although the potency and effect of rubiscolins as G-protein-biased molecules are partially confirmed, their in vitro profiles remain unclear. We, therefore, evaluated the properties of rubiscolins, in detail, through several analyses, including the CellKeyTM assay, cADDis® cAMP assay, and PathHunter® β-arrestin recruitment assay, using cells stably expressing µ, δ, κ, or µ/δ heteromer opioid receptors. In the CellKeyTM assay, rubiscolins showed selective agonistic effects for δ opioid receptor and little agonistic or antagonistic effects for µ and κ opioid receptors. Furthermore, rubiscolins were found to be G-protein-biased δ opioid receptor agonists based on the results obtained in cADDis® cAMP and PathHunter® β-arrestin recruitment assays. Finally, we found, for the first time, that they are also partially agonistic for the µ/δ dimers. In conclusion, rubiscolins could serve as attractive seeds, as δ opioid receptor-specific agonists, for the development of novel opioid analgesics with reduced side effects.